2004
DOI: 10.1182/blood-2003-08-2857
|View full text |Cite
|
Sign up to set email alerts
|

Differential processing of stromal-derived factor-1α and stromal-derived factor-1β explains functional diversity

Abstract: The chemokine stromal-derived factor-1 (SDF-1), which is constitutively expressed in most tissues as SDF-1alpha and SDF-1beta resulting from alternative gene splicing, regulates hematopoiesis, lymphocyte homing, B-lineage cell growth, and angiogenesis. Because SDF-1alpha and SDF-1beta are constitutively and ubiquitously expressed, their degradation must serve an important regulatory role. Here we show that SDF-1alpha and SDF-1beta are secreted as full-length molecules. When exposed to human serum, full-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(117 citation statements)
references
References 47 publications
(65 reference statements)
2
109
0
2
Order By: Relevance
“…This difference in activity could possibly be attributed to the differential processing of these proteins, which reduced the affinity of CXCL12␣ to bind to cells. 29 In addition, a previous study 30 showed different C-termini of CXCL12 variants may contain important molecular determinants for differences in biologic functions. This may affect binding of CXCL12 to cells either via the receptor CXCR4 or heparin sulphate, a glycosaminoglycan found ubiquitously in cell surfaces.…”
Section: Discussionmentioning
confidence: 97%
“…This difference in activity could possibly be attributed to the differential processing of these proteins, which reduced the affinity of CXCL12␣ to bind to cells. 29 In addition, a previous study 30 showed different C-termini of CXCL12 variants may contain important molecular determinants for differences in biologic functions. This may affect binding of CXCL12 to cells either via the receptor CXCR4 or heparin sulphate, a glycosaminoglycan found ubiquitously in cell surfaces.…”
Section: Discussionmentioning
confidence: 97%
“…This gives rise to six protein isoforms with shared NH 2 -termini (amino acids 1 to 68 are identical) but dissimilar COOH-termini (in length and composition). These isoforms, containing 68, 72, 98, 119, 69 and 79 amino acids respectively, display different tissue distribution patterns, different susceptibility to COOH-terminal proteolytic cleavage, different CXCR4 binding and signaling capacities and different anti-HIV activities [63][64][65][66][67][68]. Of note are their explicit variation in GAG binding affinity.…”
Section: Alternative Splicingmentioning
confidence: 97%
“…It was shown that neutralization of SDF-1 in a mouse xenograft model significantly impairs metastasis of breast cancer cells to regional lymph nodes and lung [3]. By alternate splicing SDF-1 is produced in the two isoforms SDF-1a and SDF-1b [7].…”
Section: Introductionmentioning
confidence: 99%